First Detection of Methicillin‐Resistant Staphylococcus aureus ST398 and Staphylococcus pseudintermedius ST68 from Hospitalized Equines in Spain. (17th June 2013) - Gómez‐Sanz, E.; Simón, C.; Ortega, C.; Gómez, P.; Lozano, C.; Zarazaga, M.; Torres, C.
Summary Eight coagulase‐positive staphylococci from equines with different pathologies obtained between 2005 and 2011 were investigated. Isolates were characterized by different molecular techniques (spa‐, agr‐, MLST), and clonal relatedness of strains was investigated by ApaI and SmaI PFGE. Anti‐microbial resistance and virulence profiles were determined. Six isolates were identified as Staphylococcus aureus, and two as Staphylococcus pseudintermedius. Of these, four isolates were methicillin‐resistant S. aureus (MRSA) ST398 and one S. pseudintermedius was mecA positive and typed as ST68. One MRSA ST398 strain was isolated in 2005 and might be one of the earliest MRSA ST398 descriptions in Spain. All 5 mecA‐positive strains were multidrug resistant and were isolated from hospitalized equines. Three MRSA ST398 strains carried the recently described transposon Tn559 within the chromosomal radC gene. The mecA‐positive S. pseudintermedius ST68 strain was also multidrug resistant and harboured the erm(B)‐Tn5405‐like element. This ST68 strain presented a clear susceptible phenotype to oxacillin and cefoxitin regardless of the presence of an integral and conserved mecA gene and mecA promoter, which enhances the need for testing the presence of this gene in routine analysis to avoid treatment failures. These data reflect the extended anti‐microbial resistance gene acquisition capacities of both bacterial species and evidence their pathogenic properties. The first detection of MRSA ST398 and S. pseudintermedius ST68 in horses in Spain is reported.